Direct digital radiography versus conventional radiography - assessment of visibility of file length placed in the root canal: An in vitro study - Vaiyapuri Ravi; Priyadarshini Lipee; Canagapalli Venkat Nakabushan Rao; Lakshminarayanan Lakshmikanthan (Wolters Kluwer Medknow Publications, 2012)
Aim and Objective: To compare conventional and direct digital radiography (DDR) in working length measurement of the root canal and to assess the significance of the different enhancement modes provided by the software to visualize the file length. Materials and Methods: Access cavities were prepared in 30 extracted maxillary central incisors. Size 15 k-file was introduced into the canal till it was flush with the apical foramen. The working length was calculated as 0.5 mm less than the vernier caliper measured length of each file. The files were then sealed with resin at their respective lengths. Intraoral periapical radiographs and direct digital radiographs were taken. Vernier caliper was used to measure the file length in the periapical radiographs, and standard, positive conversion, and colorize modes were used with the CDR system. A multiple regression analysis was conducted to give an accurate analysis between the actual file length and the different groups. Results: There was no statistical significance between the different groups tested. The multiple regression analysis test showed that the positive and colorize modes more accurately corresponded to the actual file length. Conclusion: Both conventional radiography and DDR can be reliably used for working length determination. The positive and colorize modes enhancement features of DDR greatly improve the visual perception, leading to more accurate measurements.